Proximity to Woodland and Landscape Structure Drives Pollinator Visitation in Apple Orchard Ecosystem - Joshi, Neelendra K.; Otieno, Mark; Rajotte, Edwin G.; Fleischer, Shelby J.; Biddinger, David J. (Frontiers in Ecology and Evolution, 2016)
Landscapes of farms and adjacent areas are known to influence abundance of various arthropods such as pollinators in commercial agricultural ecosystems. In this context, we examined the effect of heterogeneous landscapes surrounding and including commercial apple orchards on pollinator visitation and foraging distance during bloom period from 2011 to 2013 in Pennsylvania. Our results showed that the frequency of feral honeybees and solitary bee visits within an apple orchard depends on the proximity of the orchard to an unmanaged habitat (primarily comprised of forest). At the landscape scale, we found that the Mean Proximity Index, the Largest Patch Index and the Number of Patches positively correlated with the visitation rate of dominant bee taxa (Apis mellifera, Bombus spp. and solitary bees) visiting apple flowers at low spatial scales (up to 500 m around the orchards). The Mean Proximity Index at 500 m was related to bee visitation patterns, especially for solitary bees and A. mellifera. Bees in all our study sites preferred to forage in areas with large homogenous patches up to 500 m around an apple orchard. This effect can be attributed to the mass flowering of apples that formed the largest proportion of the 500 m spatial scale. The Number of Patches at 250 m spatial scale was positively correlated with bee visitation, especially Bombus spp., probably because these areas had more habitats and more resources required by these bees. We conclude that retaining unmanaged habitats closer to commercial apple orchards will maintain biodiversity within the landscapes and insure pollination services to apples.